Physiological adaptation strategies for thermoregulation in Tupaia belangeri under high-temperature environment challenge - Liu, Dongjie; Zhu, Wanlong (Frontiers in Physiology, 2025)
IntroductionTo investigate the capacity of Tupaia belangeri to withstand high-temperature environments and its adaptability to global warming trends, while examining evidence for the species’ tropical origins through thermal neutral zone analysis.MethodsThis study subjected T. belangeri, a representative mammal of the Oriental realm, to a temperature of 35 °C for 28 days to induce thermal acclimation. Body temperature (Tb) and basal metabolic rate (BMR) were measured at ambient temperatures (Ta) of 20 °C, 25 °C, 30 °C, 32.5 °C, 35 °C, and 37.5 °C, with thermal conductance (C) subsequently calculated. Latitudinal distributions and thermal neutral zone (TNZ) of 90 small mammals were compared against both normal-temperature and high-temperature acclimated T. belangeri.ResultsResults indicated that Tb increased with rising ambient temperature, averaging 39.9 °C ± 0.16 °C within the TNZ. BMR showed no significant difference within the 30 °C–35 °C range. The mean BMR was 1.60 ± 0.025 mL O2/(g·h), indicating TNZ convergence at 30 °C–35 °C under high-temperature conditions. The mean C values within this range were 0.16 ± 0.0052mL O2/(g·h· °C). Compared to previous data on normal-temperature acclimation from our laboratory, high-temperature acclimated animals exhibited elevated Tb, reduced BMR, a narrowed TNZ with an increased lower thermal neutral zone (LTNZ), and heightened C values. The TNZ of both acclimation groups in within the tropical high-temperature ranges.DiscussionThese findings collectively indicated that T. belangeri adapts to thermal stress through increased Tb, reduced metabolic rate, enhanced heat dissipation capacity, and a shift of the TNZ towards higher temperatures. Additionally, the TNZ of T. belangeri exhibited minimal fluctuations when subjected to high-temperature stress, indicating a strong adaptive capacity to warmer environments. Furthermore, the TNZ of T. belangeri is situated within the tropical high-temperature range, providing physiological evidence of its tropical origin based on the characteristics of the TNZ.